+0  
 
0
193
2
avatar

Any one know how to do this question and what the answer is ?

 Jul 16, 2019
 #1
avatar
0

The thing to expand is this 

ln(4x^2−36x+72)

 Jul 16, 2019
 #2
avatar+106539 
+1

ln(4x^2−36x+72)  =        take out the GCF  =  4

 

ln ( 4 [ x^2 - 9x + 18 ] ) =      factor  again

 

ln [ 4 ( x - 3) ( x - 6 ) ] =   

 

Use the property that.....  ln (a * b * c)  =  ln a + ln b + ln c

 

ln 4  +  ln ( x - 3)  +  ln ( x - 6)

 

 

cool cool cool

 Jul 16, 2019

17 Online Users

avatar